The effects of eco-efficiency on the profitability of ASEAN-5 companies from 2017-2019 - Abad, Angelica Sarah E. (Animo Repository, 2022)
A multitude of literature has been dedicated to researching the relationship between firms’ environmental impact and profitability. While there are numerous means to study this phenomenon, this paper aims to utilize eco-efficiency as a basis to measure the sustainability of entities and its impact on the following financial ratios: return on assets (ROA), return on equity (ROE), and return on investment (ROI). Through the use of the Refinitiv Eikon database, this study collected data on these organizations' eco-efficiency indicators and matched their impact on the previously mentioned financial ratios. The research included large ASEAN-5 companies in the Refinitiv Eikon due to the significant impact of large firms on environmental issues as well as the scarcity of studies on the matter with regard to its applicability and relevance in the Southeast Asian region. The results of this study indicate that there is no significant relationship between eco-efficiency and firm profitability; however, in ASEAN-5 countries, the prevalence of the said relationship is very weak, which can be attributed to events with multi-sectoral impacts and investors’ uncertainty towards the concept of eco-efficiency. This leaves much room for ASEAN-5 countries to revisit their current policies on sustainability disclosures to encourage more firms to disclose this information and possibly even position themselves at the forefront of the global sustainability accounting movement.